Remarks on Green function of space-fractional biharmonic heat equation using Ramanujan’s master theorem - Alireza Ansari (Kuwait Journal of Science)
In this paper, we show an addition formula for a class of Mellin transformable functions using Ramanujan’s master theorem. Also, we get the associated addition formula of Gaussian functions in terms of the Bessel functions and Green function of the space-fractional biharmonic heat equation is obtained with respect to the quartic Levy stable functions.